Prevalence and correlates of the misuse of z-drugs and benzodiazepines in the National Survey on Drug Use and Health - McHugh, R. Kathryn; Votaw, Victoria R.; Trapani, Emma W.; McCarthy, Megan D. (Frontiers in Psychiatry, 2023)
Background: Benzodiazepines and non-benzodiazepine hypnotics (z-drugs) are commonly prescribed for their anxiolytic and hypnotic properties, though they can also be misused. In studies examining the epidemiology of prescription drug misuse, these medication classes are commonly combined, rendering inadequate knowledge of their patterns of misuse. The objective of this study was to characterize the population prevalence, conditional dependence, and sociodemographic and clinical correlates of the misuse of benzodiazepines and z-drugs. Methods: Data from the National Survey on Drug Use and Health from 2015-2019 were used to estimate population-level prevalence and characteristics of benzodiazepine and z-drug misuse. Groups were derived based on past-year misuse of benzodiazepines alone, z-drugs alone, or both drug types. Unadjusted regression analyses were used to compare groups on characteristics of interest. Results: Exposure to benzodiazepines and/or z-drugs via prescription or misuse was common; however, only 2% of the population was estimated to have misused a benzodiazepine in the past year, and less than 0.5% misused z-drugs. People who misused only z-drugs were generally older, more likely to have health insurance, more educated and had less severe psychiatric symptoms. This group was also more likely to misuse to cope with sleep difficulty. Although polysubstance use was highly prevalent in all groups, people who misused z-drugs alone generally reported less polysubstance use than the other groups. Conclusions: The misuse of z-drugs is less common than benzodiazepines, and people who misuse only z-drugs appear to generally have lower clinical severity. Nonetheless, a substantial subgroup of people exposed to z-drugs report use of other substances. Further research on z-drug misuse, including consideration of whether it should be grouped with other anxiolytic/hypnotic drugs is needed.